Development of a new framework to guide, assess, and evaluate student reflections in a university sustainability course (Teaching and Learning Inquiry, 2019)
Many institutions of higher education increasingly place a focus on various forms of experiential education. While much work has been done in this and related areas, the resources currently available are not sufficient to effectively guide, assess, and evaluate student learning. Personal reflections can be used as a tool to assess student learning through experience. However, guiding students through the process, assessing their work, and providing an evaluation presents challenges for educators. A new framework, a robust rubric, and a guide that students and evaluators can use to support experiential learning through reflection are provided. The framework and resources are based on a grounded investigation of student reflections, which were compared to various evaluation models from the literature. The resources discussed in this paper have already been used in practice for over four years and with over 1,000 students. The purpose of this paper is to describe the journey leading to the development of this framework, to provide a description of the rubric and guide, and to share the lessons learned. This framework and accompanying materials will hopefully be a useful resource for instructors and students wishing to support reflection and experiential learning.